Metabolic pathway engineering of actinomycetes for novel antibiotics discovery - Baral, Bikash (fi=Turun yliopisto|en=University of Turku|, 2022)
Microbes harbouring a profound wealth of chemical space have instigated tremendous attention for developing crucial therapeutic drugs. The genes encoding the enzymes responsible for synthesizing these specialized metabolites are often organized in so-called biosynthetic gene clusters (BGCs). While these clusters are potentially capable of producing novel drug candidate, most of them remain dormant in natural environmental conditions (or settings). Microorganisms seldom synthesize substantial quantities of the desired molecules in natural settings. Harnessing the dormant compound production requires careful optimization of the host cellular machinery, which can be accomplished by thorough engineering of silent biosynthetic pathways. My target, the genus Streptomyces is endowed with tremendous abilities to secrete a diverse array of metabolites. Besides, insilico analysis of their genomic sequences reveals enormous potential to generate novel metabolites not biosynthesized in natural environmental settings. Realizing such bountiful resources, I attempt to unveil Streptomyces’ true potential to generate novel metabolites by using various approaches. In the present dissertation, various novel approaches have allowed me to unveil novel specialized metabolites encoded by otherwise silent biosynthetic clusters. For this, (i) I developed single cell mutant selection (SCMS) platform, where mutants harboring a silent promoter are probed with a double reporter system using classical mutagenesis techniques. Mutants were sorted using FACS based on expression of reporter genes and mutants generated a novel metabolite with a distinct chemical scaffold, referred to as mutaxanthene. (ii) Next approach involved binary physical interaction studies between dead yeast and Streptomyces where the contact induced production of prodigiosin. My studies identified a master-regulator, namely mbkZ, for its regulatory roles in prodigiosin production in different hosts (S. coelicolor and Streptomyces sp. MBK6). (iii) Third approach exploited CRISPR/Cas9 system to unveil the functional role of sdmA within the showdomycin biosynthetic pathway. (iv) Final approach revealed the characterization of new bacterial lineage (Streptomonospora sp. PA3) isolated from the high-salt environment, which helped me to isolate and identify a novel polyketide persiamycin A. Using these different approaches allowed me to unveil the secret knowledge sealed within biosynthetic pathways of the studied organisms. In a nutshell, adopting these techniques has helped me discover and characterize novel metabolites. I believe these strategies may aid in the fight against antimicrobial resistance and speed up the drug discovery process. Furthermore, this dissertation has not only implications for future engineering of Streptomyces to increase metabolites production, but it also illustrates a SCMS state-of-art approach for generating novel therapeutic leads.

Aktinomykeettien aineenvaihduntareittien muokkaus uusien antibioottien löytämiseksi Mikrobien tuottamat monimuotoiset luonnonyhdisteet ovat herättäneet suurta kiinnostusta lääkekehityksessä. Näiden erikoistuneiden metaboliittien tuotannosta vastaavia entsyymejä koodaavat geenit ovat yleensä järjestyneet niin sanottuiksi biosynteettisiksi geeniryppäiksi (BGC, engl. biosynthetic gene cluster). Nämä geeniryppäät saattavat tuottaa vielä tuntemattomia metaboliitteja, mutta yleensä ne ovat hiljaisia luonnollisessa ympäristössä. Yleensä mikro-organismit eivät tuota haluttua yhdistettä merkittäviä määriä luonnollisissa olosuhteissa. Näiden hiljaisten yhdisteiden hyödyntäminen lääkeaineiden kehityksessä vaatii solukoneiston huolellista optimointia, mikä voidaan saavuttaa muokkaamalla hiljaisia biosynteesireittejä. Kohdeorganismimme Streptomyces -bakteerit kykenevät tuottamaan lukuisia erilaisia sekundäärimetaboliitteja, jotka ovat kemialliselta rakenteeltaan erittäin vaihtelevia. Tämän lisäksi genomisekvenssien analyysi on paljastanut lukuisia lupaavia hiljaisia geeniklustereita, jotka saattaisivat aktivoituina tuottaa aikaisemmin tuntemattomia yhdisteitä. Tämän työn tarkoitus on käyttää useita erilaisia tekniikoita tämän hiljaisen biosynteettisen potentiaalin valjastamiseen. Väitöskirjatyössä käytin useita uusia menetelmiä hiljaisten geeniryppäiden koodaamien uusien yhdisteiden tuottamiseksi. Tätä tarkoitusta varten (i) kehitin yksisolujen mutanttivalinta (SCMS, engl. single cell mutant selection) alusta – menetelmän, missä hiljaisen geeniryppään aktiivisuutta seurataan tuplareportterisysteemillä. Seuloin menetelmällä mutanttikirjastoja reportterigeenien ilmenemisen perusteella FACS –laitteistoilla ja tuotin erityisen kemiallisen rakenteen omaavia mutaxanthene -yhdisteitä. (ii) Seuraavaksi tutkin hiivojen ja streptomykeettien fyysisen vuorovaikutuksen vaikutusta prodigiosiini –yhdisteen tuottoon. Tutkimukseni paljasti säätelygeeni mbkZ:n roolin prodigiosiinien tuotossa kahdessa eri isäntäkannassa (S. coelicolor ja Streptomyces sp. MBK6). iii) Kolmannessa menetelmässä käytin CRISPR/Cas9-menetelmää selvittääkseni sdmA geenin roolin showdomysiinin biosynteesireitillä. iv) Viimeisenä menetelmänä eristin uuden halofiilisen bakteerikannan (Streptomonospora sp. PA3) korkean suolapitoisuuden kasvuympäristöstä meren pohjasta. Kannasta eristettiin uusi persiamysiini A polyketidi. Näiden erilaisten lähestymistapojen avulla pystyin paljastamaan tutkittujen organismien biosynteettisten reittien sisälle suljetut salaisuudet. Lyhyesti, olemme pystyneet löytämään ja karakterisoimaan uusia metaboliitteja käyttämiemme tekniikoiden avulla. Uskomme, että käyttämämme strategiat auttavat kamppailuissa antibioottiresistenssiä vastaan ja nopeuttamaan uusien lääkkeiden löytämistä. Tämän lisäksi tutkielman tulokset sekä auttavat sekundaarimetabolliittien tuotannon tehostamista tulevaisuudessa streptomykeettejä muokkaamalla, että havainnollistaa SCMS –menetelmän käyttökelpoisuuden uusien terapeuttisten yhdisteiden tuotossa.